PROGRAM TOILET TRAINING BERBASIS KELUARGA BAGI ANAK CEREBRAL PALSY RINGAN TIPE DIPLEGIA - Heryati, Euis; Widiyanti, Citra R; Wibowo, Setyo W; Azizah , Farah H (Jurusan Pendidikan Luar Biasa, 2022)
This research aims to design a family-based toilet training program for children with mild cerebral palsy, diplegic type. The research method used is a case study with a qualitative approach. The subjects of this research were HW, an 8-year-old child with cerebral palsy, and her family. Data collection was carried out by interviewing parents and observing parent and child activities related to toilet training as well as toileting ability tests carried out on a child to clarify the data found. Based on the results, it was found that the parents had carried out toilet training activities but HW was still unable to do it because there were several obstacles including the motor aspect where the child was not being able to squat. Based on these problems, a program was created for parents to teach their children using task analysis and continuous training using portable toilets for children. This program specifically emphasizes several aspects, namely parental knowledge, physical readiness, intellectual and psychological readiness